Jurisprudence issues related to fasting that depend on the judge’s ruling according to the Hanbalis: Collection and Study - Almobaddal, Ibrahem Abdoalaziz Abdoallah (Journal of Islamic Sciences, 2021)
The objective of the research is a gathering and thorough examination of the matters that the judge requires within the matters pertaining to fasting in the Hanbali school of thought from one of its relied books.Guidelines which the judge needs and does not need to give an edict are given.The book Iqna'a by al- Hajjawi was chosen for which the research was to be based on after which a comparison of the remaining four schools of thought were made because the former is the primary reference for judges in this country and so is important and beneficial for judges and rulings.The research concluded in that there are three rules that the ruling of judge depends on and that this is not a point of agreement amongst the scholars.Just as the scholars differ in matter of Islamic jurisprudence likewise judges differ in matters of ruling like whether or not it was dependent on the ruling of the judge or not like in matters related to fasting, such as the beginning of Ramadhan and other months.
Keywords: Islamic Law; Judiciary; Fasting; Hanbali Doctrine